3D Porous Carbon Encapsulated SnO2 Nanocomposite for Ultrastable Sodium Ion Batteries. (1st October 2016) - Huang, Zhaodong; Hou, Hongshuai; Zou, Guoqiang; Chen, Jun; Zhang, Yan; Liao, Hanxiao; Li, Simin; Ji, Xiaobo
Graphical abstract: Highlights: 3D porous carbon encapsulated SnO2 nanocomposite is prepared via an efficient and facile in situ methodology. The composite exhibits remarkable cycle stability and notable rate capacities. This efficient in situ approach can potentially be applied to obtain other anode materials. Abstract: 3D porous carbon encapsulated SnO2 nanoparticles composite (SnO2 -PC) prepared by an efficient in situ methodology was applied as anode for sodium ion batteries (SIBs). It delivered a high reversible specific capacity of 280.1 mAh g −1 after 250 cycles at a current density of 100 mA g −1, with ultrahigh capacity retention of 91.63%. Notably, it can Exhibit 100 mAh g −1 after 1000 cycles even at a high current density of 1600 mA g −1 . These greatly enhanced electrochemical properties of SnO2 -PC composite can be attributed to the superior structure that the electrical conductivity of the composite was improved by the porous carbon matrix, moreover, it can serve as a cushion during the process of Na ion insertion/extraction into the composite. Significantly, this kind of in situ synthesis method is portable for other similar composite.